Montana small bank deposit market analysis - Patritti, Elle (Kansas State University, 2021)
Over the past few decades, the Federal Deposit Insurance Corporation (FDIC) has reported a steady increase in total deposits and a corresponding decrease in the number of commercial banks. Between 1992 and 2019, the number of banks decreased by approximately 8,000 and total deposits increased from approximately $2.5 billion to $13.6 billion. Although total deposits are increasing, it has become increasingly challenging for banks to grow core deposits that leaves them with tight liquidity metrics and forces them to borrow heavily from the Federal Home Loan Bank to fund their money supply. Costly borrowed funds and increased competitive pressure has left banks struggling to maintain sustainable returns. This trend is most relevant in small independent banks; therefore, many have left rural communities with no financial institutions. The decrease in commercial banks followed by an increase in FinTechs (online banks) resulted in numerous studies in the early 2000s that analyze the impact, if any, that the introduction of FinTechs has on the decline in traditional commercial banks. FinTechs are financial institutions that provide financial services through software or other technology platforms. Additional research has examined how banks can stabilize their funding and expand their deposit base. Researchers found that deposit levels are more stable when customers are incentivized. Those studies also conclude that FinTechs and other online financial institutions have not pushed community banks out of the market, but the upcoming shift in the primary customer base could result in a shift from borrowers who value relationship-based banking to those that do not prioritize relationships, but instead value technology that can complete the task quickly and efficiently. This thesis focuses on the deposit market in rural Montana. This study estimated the size of the total deposit market in Montana, inclusive of Federal Deposit Insurance deposits, National Credit Union Administration deposits, and online deposits at the county level. Results were used to calculate a bank’s market share of deposits on the county level. This thesis relied on discounted cash flow analysis and internal rate of return to evaluate an approach for a small Montana bank to expand its market presence into geographically isolated areas of the state. This project concluded that Montana’s rural economy, primarily those areas with an agricultural focus, creates a unique pool of deposits in towns and areas without any existing depository institution. Implementing a limited service branch in these underserved areas may provide a benefit to the bank through increased deposits and earnings growth potential. The results from this study are helpful to financial institutions that are seeking to expand their market presence in rural areas and suggests that banks looking to increase their core deposits should consider expanding to rural areas that are driven by stable industries and have limited competition from other banks.
Keywords: FinTechs; Banking industry; Agribusiness; Agricultural economics; Market analysis